A Pre-Experimental Study on Cognitive Behavioral Therapy in Enhancing Self-Confidence among Juvenile Inmates in an Indonesian Juvenile Correctional Facility - Dodi Priyatmo Silondae; Abdur Rahmat; J Jahada; A Aspin; Nadia Putri (Universitas Negeri Padang, 2026)
Children and adolescents undergoing rehabilitation at Juvenile Correctional Institutions are vulnerable to psychological problems, including low self-confidence, which may hinder rehabilitation and social reintegration. This study aimed to provide preliminary evidence on the implementation of Cognitive Behavioural Therapy to improve the mental health of juvenile inmates, particularly self-confidence, at Lembaga Pembinaan Khusus Anak Kelas II Kendari. This study employed a quantitative approach using a one-group pretest–posttest pre-experimental design. The participants consisted of eight juvenile inmates aged 15–17 years, selected through purposive sampling. The instrument used was a self-confidence scale developed based on Lauster’s five aspects of self-confidence, namely belief in one’s abilities, optimism, objectivity, responsibility, and rationality, which met the validity and reliability criteria. The cognitive behavioural therapy intervention was delivered over six group counselling sessions. Data were analysed using descriptive statistics and the Wilcoxon signed-rank test. The findings indicated an increase in the self-confidence scores of juvenile inmates after receiving the cognitive behavioural therapy intervention, with a significant difference between pretest and posttest scores. The effect size calculation yielded an r value of 0.595, which falls into the large effect category. This finding indicates that the cognitive behavioural therapy intervention had a strong influence on the observed changes in scores. Overall, the findings provide preliminary insight into the potential use of cognitive behavioural therapy as a psychological service to help improve the self-confidence of juvenile inmates in Juvenile Correctional Institutions.